PENINGKATAN PEMAHAMAN SISWA MENGENAI RECOUNT TEXT MENGGUNAKAN MEDIA ENGLISH DOMINO DI SMAN 12 MUARA BUNGO - rozanita harahap (LP3M STKIP Muhammadiyah Muara Bungo, 2022)
This Classroom action research aims to improve the students’ comprehension toward Recount Text using English Domino Game. This research was conducted in class X Science at SMAN 12 Muara Bungo. To obtain the suitable data, the researcher used students observationsheet and test. Based on the results, it can be concluded that English domino game can improve the students’ comprehension of recount text whether in process or result. The result of students observation shows the increase from 57,5% in the first cycle and increase to be 80% in the second cycle. This is categorized as very good. Meanwhile, the improvement is also showed from the test result from pre cycle to the second cycle.The data in the pre cycle was only 58% students who pass the standard. And then, it was increased at the first cycle to be 67% with the average score 72. Meanwhile, in the second was improved to be 87% dwith the average score 84.